# Calculator search results

Formula
Solve the equation
$10 \left( g+2 \right) = 6 \left( g+4 \right)$
$g = 1$
 Solve a solution to $g$
$\color{#FF6800}{ 10 } \left ( \color{#FF6800}{ g } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \right ) = 6 \left ( g + 4 \right )$
 Multiply each term in parentheses by $10$
$\color{#FF6800}{ 10 } \color{#FF6800}{ g } \color{#FF6800}{ + } \color{#FF6800}{ 10 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } = 6 \left ( g + 4 \right )$
$10 g + 10 \times 2 = \color{#FF6800}{ 6 } \left ( \color{#FF6800}{ g } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \right )$
 Multiply each term in parentheses by $6$
$10 g + 10 \times 2 = \color{#FF6800}{ 6 } \color{#FF6800}{ g } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
$10 g + \color{#FF6800}{ 10 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } = 6 g + 6 \times 4$
 Multiply $10$ and $2$
$10 g + \color{#FF6800}{ 20 } = 6 g + 6 \times 4$
$10 g + 20 = 6 g + \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
 Multiply $6$ and $4$
$10 g + 20 = 6 g + \color{#FF6800}{ 24 }$
$10 g + 20 = \color{#FF6800}{ 6 } \color{#FF6800}{ g } + 24$
 Move the variable to the left-hand side and change the symbol 
$10 g + 20 \color{#FF6800}{ - } \color{#FF6800}{ 6 } \color{#FF6800}{ g } = 24$
$10 g \color{#FF6800}{ + } \color{#FF6800}{ 20 } - 6 g = 24$
 Move the constant to the right side and change the sign 
$10 g - 6 g = 24 \color{#FF6800}{ - } \color{#FF6800}{ 20 }$
$\color{#FF6800}{ 10 } \color{#FF6800}{ g } \color{#FF6800}{ - } \color{#FF6800}{ 6 } \color{#FF6800}{ g } = 24 - 20$
 Organize the expression 
$\color{#FF6800}{ 4 } \color{#FF6800}{ g } = 24 - 20$
$4 g = \color{#FF6800}{ 24 } \color{#FF6800}{ - } \color{#FF6800}{ 20 }$
 Subtract $20$ from $24$
$4 g = \color{#FF6800}{ 4 }$
$\color{#FF6800}{ 4 } \color{#FF6800}{ g } = \color{#FF6800}{ 4 }$
 Divide both sides by the same number 
$\color{#FF6800}{ g } = \color{#FF6800}{ 1 }$
Solution search results